Research on Time of Arrival Estimation Algorithm Based on ESPRIT - Liu, Jiawei (International Journal of Computer Science and Information Technology, 2024)
The ESPRIT (Estimation of Signal Parameters via Rotational Invariance Techniques) algorithm is a high-resolution method used for estimating the Direction of Arrival (DOA) of signals. Due to its effectiveness and stability, many improvements have been proposed based on the ESPRIT algorithm, making it a prominent technique among high-resolution algorithms. In this paper, we delve into the theoretical foundations of the ESPRIT algorithm and conduct a comparative analysis with conventional Time of Arrival (TOA) estimation algorithms. Through extensive simulations, we demonstrate that the ESPRIT algorithm outperforms traditional TOA estimation methods, particularly under low signal-to-noise ratio (SNR) conditions. However, it should be noted that the ESPRIT algorithm entails a higher computational complexity. Our findings underscore the algorithm's superior performance in challenging environments, albeit with an increased computational burden.